Virulence Factors of Pseudomonas Aeruginosa and Antivirulence Strategies to Combat Its Drug Resistance - Liao, Chongbing; Huang, Xin; Wang, Qingxia; Yao, Dan; Lu, Wuyuan (Frontiers in Cellular and Infection Microbiology, 2022)
Pseudomonas aeruginosa is an opportunistic pathogen causing nosocomial infections in severely ill and immunocompromised patients. Ubiquitously disseminated in the environment, especially in hospitals, it has become a major threat to human health due to the constant emergence of drug-resistant strains. Multiple resistance mechanisms are exploited by P. aeruginosa, which usually result in chronic infections difficult to eradicate. Diverse virulence factors responsible for bacterial adhesion and colonization, host immune suppression, and immune escape, play important roles in the pathogenic process of P. aeruginosa. As such, antivirulence treatment that aims at reducing virulence while sparing the bacterium for its eventual elimination by the immune system, or combination therapies, has significant advantages over traditional antibiotic therapy, as the former imposes minimal selective pressure on P. aeruginosa, thus less likely to induce drug resistance. In this review, we will discuss the virulence factors of P. aeruginosa, their pathogenic roles, and recent advances in antivirulence drug discovery for the treatment of P. aeruginosa infections.